A COMPARATIVE STUDY OF HAND DIMENSIONS BETWEEN THAI AND OTHER POPULATIONS BY GENDER: A LITERATURE REVIEW (Proceedings of the International Conference on Public Health, 2026)
Hand anthropometric data are critical for designing hand-operated tools and devices that appropriately fit human hand dimensions. Well-fitted tools improve usability, comfort, and safety while reducing the risk of hand-related musculoskeletal disorders. A key ergonomic design factor is the anatomical difference between male and female hands, which affects grip strength, reach, and tool interaction. This study conducted a structured literature review to synthesize gender-based differences in hand anthropometry among the Thai population and compare them with international findings. Articles were retrieved using the keywords “Hand Anthropometry” and “Hand Anthropometry AND Thai” from six academic databases: Scopus, PubMed, ScienceDirect, SpringerLink, Google Scholar, and TCI. The selection process involved six exclusion steps. First, duplicates and non-anthropometric topics were removed (4 articles). Second, studies unrelated to hand dimensions were excluded (27 articles). Third, studies with fewer than five participants or overly technical focus were excluded (2 articles). Fourth, studies not reporting participant nationality were removed (50 articles). Fifth, studies involving clinical populations or robotics were excluded (12 articles). Sixth, articles lacking sex-disaggregated data or full-text access were removed (12 articles). In total, 45 articles met the inclusion criteria. The analysis showed that Thai males had hand dimensions 3.36–13.42% larger than females, with the most significant differences (over 10%) in hand width. Compared to international studies, hand length in the Thai population demonstrated a greater gender-based gap. These findings emphasize the need to integrate sex-specific anthropometric data in ergonomic design. A nationwide anthropometric survey using standardized digital tools is recommended to support inclusive product development and safety standards in Thailand.
Keywords: hand dimensions; gender; ergonomics; Thai population